VIRTUAL MODELS OF LIGHT BACKSCATTERING IN RING LASERS - A. S. Bessonov; E. A. Petrukhin (Российский технологический журнал, 2018)
The simulation of light backscattering in a ring laser is considered. It is indicated that backscattering is the main source of laser gyro errors. A mathematical description of the backscattering processes based on the determination of the complex coupling parameters of counterpropagating waves is presented. A representation of complex coupling parameters in the form of vector diagrams is proposed. It is concluded that virtual models created in graphical programming environments are most convenient for users. These models combine information contained in mathematical models and in vector diagrams. With the help of computer animation, the complex coupling parameters phase changes of counterpropagating waves during the operation of the ring laser are displayed. The simulation results are presented in various text and graphic forms. The backscattering simulation results during the laser tuning to the generation of various modes, under the influence of temperature and in the antiphase motion of piezoelectric transducers are described. The created virtual models are intended for developers of measuring systems used in the production of ring lasers and laser gyros. The obtained results allow estimating the lock.